PENGEMBANGAN MODEL GAME-BASED LEARNING MENGGUNAKAN MEDIA WORDWALL PADA PEMBELAJARAN PENDIDIKAN AGAMA ISLAM UNTUK ANAK BERKEBUTUHAN KHUSUS DI SEKOLAH LUAR BIASA FADHILAH UMMAH SUKOHARJO TAHUN 2024/2025 - Anisa Maylandari; Lailla Hidayatul Amin; Karina Sofiananda Armaza (AL-MUADDIB: Jurnal Kajian Ilmu Kependidikan, 2025)
This study aims to develop learning media find out the process of developing a Wordwall-based Game-Based Learning model in learning Islamic Religious Education for students with special needs class IX SMPLB-C at SLB Fadhilah Ummah Sukoharjo, as well as to assess the feasibility of the model developed through expert validation and limited trials on the material of mandatory and impossible properties for the Apostle in mildly disabled students. This research uses the Research and Development (R&D) method with a five-stage development model (Mantap), the stages are: (1) Preliminary Research, (2) Model Development, (3) Model Validation Test, (4) Model Trial, (5) Dissemination. Researchers used questionnaires to collect data from expert validators and students. The results showed that Wordwall-based learning media was in a very valid category as seen from the results of material expert validation a score of 86.53%, media expert of 97.36%, and educators of 95.83%. The results of the student response questionnaire from the limited trial showed that students' responses to the learning media developed were classified as very good. In conclusion, Wordwall media through the Game-Based Learning approach is a very feasible and interesting media to be used in learning Islamic Religious Education for students with special needs.